Deformation of 3D printed agglomerates: Multiscale experimental tests and DEM simulation. (18th May 2020) - Ge, Ruihuan; Ghadiri, Mojtaba; Bonakdar, Tina; Zheng, Qijun; Zhou, Zongyan; Larson, Ian; Hapgood, Karen
Graphical abstract: Highlights: A coordinated multiscale approach is proposed for comparing and validating particle models. Multi-material 3D printing technology was used to produce agglomerates with tuneable properties. Doublets were experimentally characterised to obtain bonding parameters with defined physical properties. DEM combined with TBBM model was used to simulate the agglomerate deformation. The DEM simulation and experimental results showed good agreement at the elastic deformation stage. Abstract: Agglomerates are widely used in industry, and their mechanical properties are of great interest. In this work, we propose a new concept of using a coordinated multiscale approach to match the physical and digital agglomerate structures and properties. By using a multi-material 3D printing technology, the inter-particle bond properties and agglomerate structures could be precisely controlled and replicated. Quasi-static compression tests have been carried out for the 3D printed samples at different scales. A Timoshenko Beam Bond Model (TBBM) with bond properties matching those of the 3D printed agglomerates is used to describe bond deformations. Discrete Element Method (DEM) is then employed to simulate the agglomerate crushing process. The results show that for both agglomerate structures, the DEM simulation and experimental results show good agreement at the initial elastic deformation stage. This work opens up the chance for significant advances in agglomerate deformation and breakage modelling in future.